Study of the effectiveness analysis of fingerprints as a website-based presence at NU Darussalam Vocational School - Bangun Setywan; Ratna Mustika Yasi; Muhammad Zainal Roisul Amin (Journal of Educational Engineering and Environment, 2022)
SMK NU Darussalam Srono is a SMK that still applies conventional attendance recording by recording student attendance monthly in attendance books, so it is necessary to apply computerized attendance recording by utilizing a website-based concept that is more efficient and facilitates administrative processes. Based on the research results, this website-based fingerprint presence tool can be used and implemented at SMK NU Darussalam and has been shown to be effective. This is evidenced by the validation results of material experts of 79.165% (Effective) and 53.33% (Effective) of media experts. Based on the effectiveness questionnaire questionnaire distributed to students and teachers after one month of implementation, the results obtained were 89.15% (effective) for teachers and 83.26 (effective) for students.